High-Fidelity Simulation in Occupational Therapy Curriculum: Impact on Level II Fieldwork Performance - Rebecca Ozelie; Catherine Both; Emma Fricke; Carolyn Maddock (Scholarworks @ WMU, 2016)
Simulation experiences provide experiential learning opportunities during artificially produced real-life medical situations in a safe environment. Evidence supports using simulation in health care education yet limited quantitative evidence exists in occupational therapy. This study aimed to evaluate the differences in scores on the AOTA Fieldwork Performance Evaluation for the Occupational Therapy Student of Level II occupational therapy students who received high-fidelity simulation training and students who did not. A retrospective analysis of 180 students from a private university was used. Independent samples nonparametric t tests examined mean differences between Fieldwork Performance Evaluation scores of those who did and did not receive simulation experiences in the curriculum. Mean ranks were also analyzed for subsection scores and practice settings. Results of this study found no significant difference in overall Fieldwork Performance Evaluation scores between the two groups. The students who completed simulation and had fieldwork in inpatient rehabilitation had the greatest increase in mean rank scores and increases in several subsections. The outcome measure used in this study was found to have limited discriminatory capability and may have affected the results; however, this study finds that using simulation may be a beneficial supplement to didactic coursework in occupational therapy curriculums.